On the need for long-term care and the role of the state in providing it - Dragićević Marija (Zbornik Radova Pravnog Fakulteta u Nišu)
As societies move through the process of industrialization and development, they experience a demographic transition that results in an increase in longevity, an increase in the number of elderly people in the total population, and the survival of subpopulation groups that in the past often failed to survive early childhood. Although the effect of increased life expectancy on the health status and prevalence of disability is not clear, and the impact of advances in medical science and practice on the quality of life of the elderly is not easy to assess, the extension of life expectancy undeniably results in an increasing number of elderly people who need some service from the long-term care system. This demand is further strengthened by the increasing frequency of some form of disability among other categories of the population, as well as the change in family models that resulted in the transformation of the way of providing long-term care from an almost exclusive focus on geographically close family that provides unpaid direct daily care to an increasing reliance on care mechanisms from a distance. Despite doubts about the possible interplay of the mentioned demographic, family and health status trends of the population, there is little doubt about the increasing need for the establishment of a long-term care system for persons dependent on other people's care and assistance. This article discusses the aforementioned need and the role of the state in providing it.